To simplify the equation, we need to find a common denominator for the fractions on the left side of the equation.
1/x + 3/x = (1+3)x/(x(x-3)) = 4x/(x(x-3))
So the left side of the equation becomes:
4x/(x(x-3)) = ax + b/x² - c
Now we can try to find the values of a, b, and c by comparing the numerators on both sides of the equation.
4x = ax(x-3) + b
Expanding the right side, we get:
4x = ax² - 3ax + b
Now we need to find a, b by comparing coefficients:
a = 4 (coefficient of x² term)
-3a = 0 (coefficient of x term on both sides of the equation)
b = 0 (constant term)
Therefore, a = 4, b = 0, and c = 3 (coefficient of x term in the denominator).
So the simplified equation is: 4x/(x(x-3)) = 4x/x².
Perform the operation and simplify such that: 1/x+3 + 3/x-3 = ax+b/x²-c
a=
b=
c=
1 answer